Кинематическая миграция поля преломленных волн при формировании изображения среды по данным ГСЗ - Верпаховская, А.О. (Геофизический журнал, 2014)
While producing the image of environment we need to have some a-priori information of its velocity model. Finite-difference kinematic migration of the field of refracted waves makes possible to describe the deep location of refracting boundary as well as the values of velocity in overlying series that is enough for subsequent formation of environment image applying dynamic migration. An algorithm has been proposed and software support of finite-difference kinematic migration of the field of refracted waves in case of formation of the image of environment according to DSS data taking into account their special features, which effectiveness is demonstrated by model and practical materials.